The effectiveness of english teaching materials based on content and language-integrated learning (CLIL) to increase the technological pedagogical content knowledge (TPACK) of prospective biology teachers - Aulia Dwi Amalina Wahab; A. Wahab Jufri; Imam Bachtiar; Nina Nisrina (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to examine the use of English in the Biology handbook through a learning approach based on Content Language Integrated Learning (CLIL) to increase the Technological Pedagogical Content Knowledge (TPACK) for prospective teacher students in the Biology Education Study Program at the University of Mataram. This research was conducted using a quasi-experimental approach with multiple group pre-test and post-test patterns. The test subjects and units of analysis were all second-semester students taking English for Biology courses at the FKIP Biology Education Study Program in the 2021/2022 academic year consisting of 6 classes, namely A, B, C, D, E, and F. TPACK data were analyzed using the N-gain. The N-gain test is used to measure the difference between the post-test and the pre-test. Based on the results of data analysis, it is known that there is an increase in students' TPACK ability to get N-gain values of 91%, 56%, 67%, 64%, 66%, and 61% for classes A, B, C, D, E, and F. The average value of N-gain for TPACK of biology education students is 68, which is quite effective. Therefore, it can be concluded that the English handbook through a CLIL-based learning approach contributes quite effectively to increasing the TPACK of prospective Biology teacher students.